An induction of Undecylprodigiosin Production from Streptomyces coelicolor by Elicitation with Microbial Cells Using Solid State Fermentation - Kadhum Luti, Khalid Jaber; Yonis, ReemWaleed (Iraqi Journal of Science, 2023)
Red pigmented undecylprodigiosin produced by Streptomyces coelicolor (A3)2 is apromising drug owing to its characteristics of antibacterial, antifungal,immunosuppressive and anticancer activities. The culture of S. coelicolor in liquidmedium produces mainly the blue pigmented actinorhodin and only low quantities ofundecylprodigiosin. From an industrial point of view, it is necessary to find a strategy toimprove undecylprodigiosin production. The present study provides evidence thatcultivation of S. coelicolor on solid substrate resulted in a reversal in this pattern ofantibiotic production as the production of undecylprodigiosin was significantly increasedand actinorhodin was completely suppressed. Four different solid substrate (wheat bran,soya bean ground, rice husk and ground corn) were tested for their ability to support themaximal production of undecylprodigiosin in solid state fermentation. Wheat branshowed the highest production of undecylprodigiosin, starting from the first day ofincubation at a moisture level of (1:1 weight: volume) and reaching its maximum of 16mg/gds on the fourth day. In addition, we report the exploitation of the interspeciesinteraction in order to enhance undecylprodigiosin production by introducing live ordead cells of E. coli, Bacillus subtilis and Saccharomyces cerevisiae, separately, toStreptomyces coelicolor solid substrate fermentation. Our results revealed a significantincrease in the production of undecylprodigiosin in the elicited cultures compared withcontrol. The maximum enhancement occurred in the culture elicited with the live cells ofB. subtilis with an increase of 2-fold compared with control.